Median codeword Shift (MCS) technique for PAPR reduction with low complexity in OFDM system - Mohd Danial Rozaini; Azlina Idris; Darmawaty Mohd Ali; Ezmin Abdullah (International Journal of Electrical and Computer Engineering (IJECE), 2019)
With the rapid development of today’s communication technology, the need for a system capable to improve spectral efficiency, high data rates and at the same time can reduce inter-symbol interference (ISI) is necessary. Orthogonal Frequency Division Multiplexing (OFDM) meet all the requirements needed. However, the high peak to average power ratio (PAPR) has become its major obstacle. This paper is focusing on the development of Median Codeword Shift (MCS), which a new PAPR reduction technique with the capability to reduce the computational complexity of the system. This can be achieved through codeword structure alterization and bit position manipulation by utilizing the circulant shift process. The simulation results revealed that the proposed technique overwhelm conventional OFDM and SCS with 24% improvement and 0.5 dB gap from SCS. In fact, the proposed technique possess a lower computational complexity by reducing 16.67% of the use of IFFT block in the system in contrast with SCS technique.